KAJIAN ENERGI PENERAPAN BUILDING APPLIED PHOTOVOLTAICS (BAPV) PADA ATAP GEDUNG POLITEKNIK ACEH - Rachmad Ikhsan; Ira Devi Sara; Rakhmad Syafutra Lubis (Politeknik Aceh, 2016)
The problem in this research involves undeveloped BAPV usage yet and also still minimal the usage of solar modules application on a building in the region of Banda Aceh, especially in office building, institution building, and others. For these reasons, the authorconducts an energy assessment of BAPV system. The method used in this study of energy is simulation using helioscopesoftware and theoretical calculations. The monthly average of electrical energy required in 2015 was 12.3 MWh per month or 411 kWh per day, if the estimated rise of energy usage by 10% in the next year, the energy generated annually from BAPV system on the roof of the Aceh Polytechnic Building at 18 MWhper monthor600.5 kWh per day with a capacity charge controller used is 5861.8 A and the capacity of used battery is 64.487 Ah, or 172 batteries with a voltage of 12 volt with each capacity of 375 Ah and theused panel tilt angleis 25o.